Aprendizagem da docência: um estudo com professores do curso pré-vestibular da UFSCar - Moraes, Alessandra Cardoso de (2005)
This research is about an inquiry of the teachers learning process in the CPV (Curso Pré- Vestibular da Universidade Federal de São Carlos). It aims at analysis of the learning built by the teachers during their practices in CPV, under their own perspective. Thus some elements are being considered, for instance: the scholar history of the seven teachers, their initial formation and context factors making relation with different experiences with the CPV team work. This study relies on educational literature from teachers formation area and indicates the teachers learning occur inside a continuum and through reflection, in and about the teaching, the teachers acquire new knowledge and rebuild their practice. In this perspective, the learning coming from the teacher s experience has an important figure in this context. Based on the data of interview with participants it is possible to observe teachers passing through stabilization process, when they improve and/or modify their teaching strategy to overcome some found difficulties. When they feel more safety about some components of the how to teach , the teachers pass through a process of worry decentralization related with their own performances and actions to focus on students and observing their life s context, difficulties, anguish and comprehensions about what is taught. Teachers begin to re-judge the teaching in accord with the students necessity and the analysis of the life s experience. The group activities that have been done in CPV can develop the reflexive process related with features of the students who frequent the course. Besides, the teachers involve themselves into outclasses areas bringing into relation with the management and organization which characterizes the CPV project. They can be part of a project s coordination group or be a coordinator of their own work area. In this professional formation places, they share with partners their anguish and suggest solutions, there are deals about process, contents and dynamics.